La risonanza magnetica pesata in diffusione (DWI) per la quantificazione del volume delle cisti e la caratterizzazione del tessuto non cistico nella malattia policistica renale: lo studio dell'Istituto Mario Negri - Ariela Benigni (AboutScience Srl, 2023)
Beyond total kidney and cyst volume, non-cystic tissue plays an important role in autosomal dominant polycystic kidney disease (ADPKD) progression. Recent advancements in magnetic resonance imaging (MRI) offer the possibility to study kidney microstructure and function, besides anatomy. In particular, Diffusion Weighted Imaging (DWI), an MRI technique sensitive to water molecule motion (diffusion) in biological tissues, allows to investigate microstructure. This study, recently published in the European Radiology scientific journal, proposes and preliminary validates a novel method to segment cystic and non-cystic volume on DWI scans from ADPKD patients. The study also provides evidence of DWI potential in characterising non-cystic kidney tissue, denoted by higher diffusion and lower perfusion than healthy tissue, in line with its fibrotic nature and the likely presence of microcysts. Overall, this study provides evidence in support of DWI potential in ADPKD. DWI could complement existing biomarkers for noninvasively staging, monitoring, and predicting ADPKD progression and evaluating the impact of novel therapies, possibly targeting damaged non-cystic tissue besides cyst expansion.